Grupo de Capoeira Angola Malta Nagoa: estudo sócio-antropológico de um patrimônio cultural negro - Alves, Carine Costa (2018)
Capoeira, currently recognized as Intangible Heritage of Brazilian Culture and, moreover, a Cultural Patrimony of Humanity is teaching, foundation, ancestry, and a philosophy of life. As a black cultural heritage it involves fighting, dancing, playing, music and art. This study presents Capoeira Angola through an anthropological analysis of the Capoeira Angola Group Malta Nagoa, located in the city of Uberlândia, state of Minas Gerais. A group that has as its mobilizing principles the lineage of Master João Pequeno de Pastinha and the social projects, with an associative spirit and social support, as well as a support network. This research emphasizes a movement that originates in African civilizations, through the period of enslavement and diaspora, Capoeira slave and Capoeira criminalized, and Capoeira as patrimony. Highlighting in this course the figures of Master Pastinha and Master João Pequeno de Pastinha, as well as of Master Guimes, the main character of this story. From this qualitative analysis, ethnographies of two moments were developed: the commemorative festivities of the Capoeira Angola Group Malta Nagoa and the Centenary of Master João Pequeno de Pastinha. Finally, it is important to emphasize that the present research has as general objective to understand what is mobilized by the Group, its perceptions and social representations, having as final product descriptions, analyzes and the ethnography. Mobilizations that stand out for the support and welcome "the other", of all of us, but also materializing in the various social projects and valorization of our African, Black, Afro-Brazilian origin. We still had the pretension to follow a path in the decolonial studies, transgressing directives and conducts imposed by the colonizers.